Розробка застосунку психологічної допомоги при повітряній тривозі - Савєльєва, В. Ю. (ХНУРЕ, 2024)
In today's world people often encounters circumstances that in one way or another affect their stress level. Considering this, the creation of applications for psychological help has become relevant, so the user can turn to these applications to prevent and overcome states of anxiety, panic, etc.
Keywords: психологічна допомога; повітряна тривога; веб-додаток